Pregunta
1. \( 25 a^{2}-16 \) 3. \( 2 a^{2}+2 b^{2} \) 5. \( x^{2} y^{2}-1 \) 7. \( 28 x^{3}-63 x b^{2} \) 9. \( (2 x+3 y)^{2}-9 \) 11. \( 4 x^{2}-(3 x-2 y)^{2} \) 13. \( 25 a^{2}(a-3 b)+9(3 b-a) \)
Ask by Powell Stuart. in South Africa
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
1. \( 25 a^{2} - 16 = (5a - 4)(5a + 4) \)
2. \( 2 a^{2} + 2 b^{2} = 2(a^{2} + b^{2}) \)
3. \( x^{2} y^{2} - 1 = (xy - 1)(xy + 1) \)
4. \( 28 x^{3} - 63 x b^{2} = 7x(2x - 3b)(2x + 3b) \)
5. \( (2x + 3y)^{2} - 9 = (2x + 3y - 3)(2x + 3y + 3) \)
6. \( 4x^{2} - (3x - 2y)^{2} = (2y - x)(5x - 2y) \)
7. \( 25 a^{2}(a - 3 b) + 9(3 b - a) = (a - 3b)(5a - 3)(5a + 3) \)
Solución
Sure, let's factor each of the given expressions step by step.
---
### **1. \( 25 a^{2} - 16 \)**
This is a **difference of squares**, which can be factored using the formula:
\[
A^2 - B^2 = (A - B)(A + B)
\]
Here, \( A = 5a \) and \( B = 4 \).
**Factored Form:**
\[
25 a^{2} - 16 = (5a - 4)(5a + 4)
\]
---
### **3. \( 2 a^{2} + 2 b^{2} \)**
First, factor out the common factor of **2**:
\[
2 a^{2} + 2 b^{2} = 2(a^{2} + b^{2})
\]
The expression \( a^{2} + b^{2} \) does not factor further over the real numbers.
**Factored Form:**
\[
2 a^{2} + 2 b^{2} = 2(a^{2} + b^{2})
\]
---
### **5. \( x^{2} y^{2} - 1 \)**
This is also a **difference of squares**. Let \( A = xy \) and \( B = 1 \).
**Factored Form:**
\[
x^{2} y^{2} - 1 = (xy - 1)(xy + 1)
\]
---
### **7. \( 28 x^{3} - 63 x b^{2} \)**
First, factor out the **greatest common factor (GCF)**, which is \( 7x \):
\[
28 x^{3} - 63 x b^{2} = 7x(4x^{2} - 9b^{2})
\]
Notice that \( 4x^{2} - 9b^{2} \) is a **difference of squares** where \( A = 2x \) and \( B = 3b \).
**Fully Factored Form:**
\[
28 x^{3} - 63 x b^{2} = 7x(2x - 3b)(2x + 3b)
\]
---
### **9. \( (2x + 3y)^{2} - 9 \)**
Recognize this as a **difference of squares**, with \( A = (2x + 3y) \) and \( B = 3 \).
**Factored Form:**
\[
(2x + 3y)^{2} - 9 = (2x + 3y - 3)(2x + 3y + 3)
\]
---
### **11. \( 4x^{2} - (3x - 2y)^{2} \)**
This is a **difference of squares**, where \( A = 2x \) and \( B = (3x - 2y) \).
**Factored Form:**
\[
4x^{2} - (3x - 2y)^{2} = (2x - (3x - 2y))(2x + (3x - 2y))
\]
Simplify the factors:
\[
= (-x + 2y)(5x - 2y) = (2y - x)(5x - 2y)
\]
---
### **13. \( 25 a^{2}(a - 3 b) + 9(3 b - a) \)**
First, rewrite the expression to identify a common factor:
\[
25 a^{2}(a - 3b) + 9(3b - a) = 25a^{2}(a - 3b) - 9(a - 3b)
\]
Factor out the common term \( (a - 3b) \):
\[
= (a - 3b)(25a^{2} - 9)
\]
Notice that \( 25a^{2} - 9 \) is a **difference of squares**, where \( A = 5a \) and \( B = 3 \).
**Fully Factored Form:**
\[
25 a^{2}(a - 3 b) + 9(3 b - a) = (a - 3b)(5a - 3)(5a + 3)
\]
---
Feel free to ask if you need further explanations or assistance with these problems!
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
The Deep Dive
The expression \( 25 a^{2}-16 \) is a classic example of a difference of squares, which can be factored as \( (5a - 4)(5a + 4) \). This technique comes in handy for simplifying many expressions and is often encountered in algebraic manipulations. In real life, factoring polynomials is vital in various scenarios, including computer graphics, where polynomial functions are used to model curves and surfaces. Factorization helps in optimizing calculations and rendering shapes accurately, making it a fascinating intersection of math and technology.
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium